Listeria monocytogenes in Food Matrix: Frequency and Effect of Antagonist Microbial - El Habib, Fatima; Ennaji, My Mustapha; Ouardi, Abdelmoula El; Senouci, Samira (Pakistan Journal of Nutrition, 2014)
Listeria monocytogenes causes septicemia, infections of the central nervous system (meningitis and meningoencephalitis) and abortions. Listeriosis occurs primarily in people at risk, such as the elderly, pregnant women and their newborns or people with a serious weakening the body or those whose cellular immunity is impaired. L. monocytogenes is a bacterium widely distributed in the environment. Its ability to persist in the industrial environment was the cause of food contamination from raw animal or plant and was a recurring problem for the food industry, despite the use of the cold chain. L. monocytogenes is a pathogen transmitted through contaminated food. It is responsible for serious infections sometimes fatal, operating mainly as sporadic sometimes epidemic. To assess the presence of L. monocy togenes in region of Rabat and determine their effect on the microbiological quality products from different food matrices, we conducted this study for three years (2009-2011). In total, 2311 samples were collected. Examination of these samples resulted in 59 samples which were positive for L. monocytogenes in: Red meat products 3.7%, white meat products 7.1%, prepared meals 1.25%, the salads 4.19%, dairy 2.34% and pastries 1.3%. However, this pathogen was absent in other analyzed samples (fishery products, creams and ice creams). Although the level of contamination by L. monocytogenes is generally low. In addition our results suggest the intervention of antagonist microbial mechanisms which may affect the survival of this pathogen.